Multiphase Shock Cooling Emission in Ultrastripped Supernovae - Annastasia Haynie; Samantha C. Wu; Anthony L. Piro; Jim Fuller (The Astrophysical Journal, 2025)
Ultrastripped and Type Ibn supernovae (USSNe and SNe Ibn, respectively) are fast-evolving, hydrogen-poor transients that often show signs of interaction with dense circumstellar material (CSM). S. C. Wu & J. Fuller identify a mass range for helium-core stars in which they expand significantly during core oxygen/neon burning, resulting in extreme late-stage mass loss in tight binaries ( P ∼ 1–100 days). Here we explore the resulting light curves from a subset of models from S. C. Wu & J. Fuller and find that in some cases they can exhibit two phases of shock cooling emission (SCE). The first SCE is attributed to the circumbinary material, and the second is from the extended helium-burning envelope of the exploding star. Since SCE luminosity is roughly proportional to the initial radius of the emitting material, events that exhibit both phases of SCE provide the exciting opportunity of measuring both the extent of the CSM and the radius of the exploding star. These light curves are explored with both analytic arguments and numerical modeling, and from this we identify the parameter space of CSM mass, helium envelope (HE) mass, and nickel mass, for which the HE SCE will be visible. We provide a qualitative comparison of these models to two fast-evolving, helium-rich transients, SN 2019kbj and SN 2019dge. The similarity between these events and our models demonstrates that this extreme binary mass loss mechanism may explain some SNe Ibn and USSNe.